Odpowiedzi

Najlepsza Odpowiedź!
2010-02-15T11:31:35+01:00
Oblicz :
a) √256=16
b) √1,69=1,3
c) √6¼=√6,25=2,5
d) ∛512=8
e) ∛1,331=1,1
f) ∛3⅜=³√27/8=3/2


oblicz:
√3² : 3⁻⁴ * 9⁻² + (2²)³ * 4⁻¹ =
3:(1/3)⁴*(1/9)²+4³*(1/4)=
3*81*1/81+64*1/4=
3+16=19
√19 i tego już nie da się wyciągnąć spod pierwiastka
chyba że ten pierwszy pierwiastek odnosi się do całości
to wtedy
√9:(1/3)⁴*(1/9)²+4³*(1/4)=
√9*81*1/81+64*1/4=
√9+16=√25=5
2010-02-15T11:40:40+01:00
A) √256=16
b) √1,69=1,3
c) √6¼=25
d) ∛512=8
e) ∛1,331=1,1
f) ∛3⅜=3/2

√ 3² : 3⁻⁴ * 9⁻² + (2²)³ * 4⁻¹ =
√ 9 : 1/81 * 1/81 + 2⁶ * 1/4=
√ 9 * 81 * 1/81 + 64 * 1/4=
√ 9 + 16 =
√25 = 5

Na 100% dobrze
Pozdro